International demand for nature-based tourism in Costa Rica: Socio-demographic and travel indicators - Villalobos Céspedes, Daniel (2012)
Demand for tourist activities related to natural spaces and wildlife has increased over recent years. This paper analyses the influence of socio-demographic and travel indicators on international demand for such tourism in Costa Rica. Using discrete choice models, a range of principal activities is studied: hiking, visits to volcanoes, observation of flora and fauna, bird-watching and canoeing. The results show the favourable influence on demand of variables such as family, travel with partners and country of origin, providing orientation for policies and strategies of the nature-based tourism in Costa Rica, as well as indicators for other countries interested in developing this sector.